Severity of pneumococcal versus non‐pneumococcal acute otitis media in children. (August 2015) - Ovnat Tamir, S.; Roth, Y.; Goldfarb, A.; Grotto, I.; Marom, T.
<x xml:space="preserve">Abstract</x> Background Pneumococcal acute otitis media (AOM) has been previously considered as a more severe disease than that caused by other otopathogens, based on clinical and/or otologic scores. We sought to test this hypothesis in the pneumococcal conjugated vaccine (PCV) era. Methods Children <6 years who presented with 'severe' AOM episodes with middle ear fluid (MEF) cultures during 2008–2013 were retrospectively identified. 'Severe' AOM episodes were considered if tympanocentesis was required or if spontaneous otorrhea was present. Data were extracted for demographics, clinical and laboratory tests. Children were categorised according to their PCV status as 'unimmunised' or 'PCV7/PCV13 immunised' and according to their MEF culture results into the 'pneumococcal' or the 'non‐pneumococcal' group. Leukocytosis was defined as white blood cells (WBC) count >15 000/μL, and elevated C‐reactive protein (CRP) level was considered as >50 mg/L. Results Of 295 eligible AOM episodes, 106 (36%) were culture positive. Children in the pneumococcal group (65, 61%) had a significantly higher WBC counts and higher CRP levels, were more often <2 years old and were more prone to complicate with acute mastoiditis (AM), compared to children in the non‐pneumococcal group, P = 0.03, P = 0.02, P = 0.04 and P = 0.03, respectively. In the pneumococcal group, unimmunised children had higher WBC counts when compared with PCV13‐immunised children (P = 0.04), but there were no appreciable differences in CRP levels between unimmunised and PCV7/PCV13‐immunised children. Conclusion Pneumococcal AOM is associated with higher leukocytosis and CRP levels than non‐pneumococcal AOM. Circulating Streptococcus pneumoniae strains causing 'severe' AOM in PCV13‐immunised children yielded lower inflammatory responses when compared with unimmunised children.